2014
DOI: 10.1177/000313481408001001
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Cystic Neoplasms of the Pancreas: Are we Overestimating Malignant Potential?

Abstract: Surgical resection is recommended for all mucinous cystic neoplasms (MCNs) of the pancreas as a result of: 1) lack of an accurate tumor marker for invasive cancer; 2) young age at diagnosis; and 3) historical studies revealing 36 per cent incidence of malignancy in resected lesions. This study compares the clinicopathologic and prognostic features of our series of resected MCNs to recent studies using the current International Association of Pancreatology (IAP) system. Thirty-eight resected MCNs were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Similarly, a study from France of the preoperative HR imaging features of MCN concluded that the detection of an MN is strongly suggestive of malignancy whereas a cyst <4 cm harbors no risk of malignancy . Indeed, studies have suggested that there is an overestimation of malignancy risk in MCN, and that MCNs have a very low prevalence of malignancy with excellent outcomes regardless of histological grade . As such, in 2015, the American Gastroenterological Association published guidelines for the management of patients with asymptomatic neoplastic cysts that advocated for a higher threshold for surgical resection, requiring at least 2 HR imaging features or positive cytology …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study from France of the preoperative HR imaging features of MCN concluded that the detection of an MN is strongly suggestive of malignancy whereas a cyst <4 cm harbors no risk of malignancy . Indeed, studies have suggested that there is an overestimation of malignancy risk in MCN, and that MCNs have a very low prevalence of malignancy with excellent outcomes regardless of histological grade . As such, in 2015, the American Gastroenterological Association published guidelines for the management of patients with asymptomatic neoplastic cysts that advocated for a higher threshold for surgical resection, requiring at least 2 HR imaging features or positive cytology …”
Section: Discussionmentioning
confidence: 99%
“…Because the typical patient is a middle‐aged female, the current recommendation in the United States is surgical resection given the relative ease of the usual distal pancreatectomy compared with the expense and anxiety of life‐long surveillance for malignant progression . However, more conservative management options have been increasingly explored …”
Section: Introductionmentioning
confidence: 99%
“…8,27,28 Moreover, combining the results of six major studies that met International Academy of Pathology criteria for diagnosis of MCNs showed that only 0.26% of MCNs <3 cm in diameter were malignant. [28][29][30][31][32][33] Indeed, the authors of these recent studies suggest following up MCNs of small dimensions and in the absence of solid components. [34][35][36] Among all PCNs, IPMNs represent by far the most debated entity in terms of assessing the reliability of the guidelines.…”
Section: The Management Of Pancreatic Cysts Beyond the Guidelinesmentioning
confidence: 99%
“…They were initially described in 1978 as mucin-producing non-ductal cystic tumors (5,11,12), and subsequently divided in 1996 into the two different entities, MCN and IPMN. MCNs were defined as lesions with inner epithelial mucin-secreting cells and a surrounding dense ovarian type stroma (1,3,(6)(7)(8)(12)(13)(14)(15)(16)(17)(18)(19). In 2006, the IAP guidelines added that an MCN could not have communication with the pancreatic duct (1,3,12,14,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…MCNs were defined as lesions with inner epithelial mucin-secreting cells and a surrounding dense ovarian type stroma (1,3,(6)(7)(8)(12)(13)(14)(15)(16)(17)(18)(19). In 2006, the IAP guidelines added that an MCN could not have communication with the pancreatic duct (1,3,12,14,(16)(17)(18). Preoperative differential diagnosis of MCNs with other cystic tumors is not always easy, especially with certain IPMN (3,7,9).…”
Section: Introductionmentioning
confidence: 99%